open-source enterprise resource planning system Odoo roll in rationalizing the costs of the Ishtar Sheraton Hotel/ applied research (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The Accommodation industry in Iraq suffers from many problems, especially after 2003, when the Accommodation industry was exposed to many crises due to the security and political situation in Iraq, which negatively affected the administrative operations inside the industry and created many problems, the most important of which are deterioration, high costs and poor performance, so some hotel administrations sought To find alternative solutions that help in the advancement of hotels, one of the proposals is to go to technology, as technology is currently one of the most important solutions to solve large complex problems, as the world has turned to automation to solve complex problems such as increasing production, reducing costs, and raising efficiency through the application of enterprise resource planning systems. As this study aims to ​​show the impact of the application of the enterprise resource planning system on hotel costs, to provide an integrated costing system whose results can influence management decisions and show the differences.The study aimed to present modern mechanisms in cost rationalization and to clarify the role of the open-source enterprise resource planning system Odoo in rationalizing costs and providing an integrated cost system whose results can influence the decisions of the management of the company in question.One of the important conclusions that the research led to is the weak administrative organization in the hotel sector, as most of the transactions take many days to complete, and the material exchange transaction is usually prepared two or three days after the party is completed, and the hotel industry in Iraq’s dependence on the Iraqi government indirectly makes it vulnerable to high impact The changes that occur in the political arena, which lead to an increase in costs due to the poor management experience of many department managers, and the high percentage of spoilage in the stores of raw materials due to the lack of a recipe and standard costs for dishes, which causes withdrawals of materials from the main stores in an unorganized manner, meaning that more than Need or less, and this mechanism leads to the retention of quantities of perishable raw materials in non-refrigerated sub-stores and thus spoilage of raw materials.